A dynamic model for calculating methane emissions from digestate based on co-digestion of animal manure and biogas crops in full scale German biogas plants. (February 2015) - Muha, Ivo; Linke, Bernd; Wittum, Gabriel
Highlights: Dynamic mathematical model for methane emissions from storage tanks. Methane emissions in storage tanks from crops are low. Emissions in storage tanks from manure are high; the storage tank should be covered. Abstract: The focus of this work is the development of a model for the estimation of methane emissions for storage tanks of biogas plants. Those can be estimated depending on (i) hydraulic retention time in the digester, (ii) an arbitrary removal rate of the digestate from the storage tank and (iii) arbitrary temperature conditions in the storage tank. Furthermore, the model is capable of considering an arbitrary mixture of manure and crops in the input material. The model was validated by data from 21 full scale biogas plants in Germany digesting cow manure and crops. A realistic scenario for the removal rate and temperature conditions in the storage tank was then investigated and special emphasis was given to the effect of hydraulic retention time and proportion of crops in the mixture on the input VS methane yield from the digester and the storage tank.